(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The Infertility wing dept. of gyne & obst at BSMMU provides services to the infertile couples who are referred from primary care levels and who cannot afford the expensive private facilities. The semen analysis is performed for the male partners of infertile couples at the Andrology Lab of BSMMU for detecting male factor abnormalities. Objectives: The objective of the study is to find out the pattern of semen parameters in our population and to find out the frequency and type of abnormal semen parameters. Methods: This is a retrospective descriptive study of the semen analysis performed at the Andrology Lab of BSMMU during the year 2011. A total of 200 consecutive samples were analysed. The procedure and reference values were according to the WHO guidelines 1999. Results: Semen parameters were abnormal in 38.5% of semen analysis. Severe male factor abnormality (azospermia and severe oligospermia combined) was in 28%. Sperm concentration had the highest variability followed by motility and morphology respectively in the n01moozospermic males. Conclusion: Severe oligospennia and azospermia are the most common abnormalities among the infertile men presenting at the Infertility unit ofBSMMU. It is recommended that the service at the Infertility wing of BSMMU should be more focused on these male factor abnormalities.